Exploring implementation factors influencing business-to-customer (B2C) e-Commerce - Paris, Deborah Libu (Amer Scientific Publishers, 2015)
The Internet makes it possible for consumers to shop without going to a physical store. As online shopping is getting to be more pronounced, retailers opted to make use of the Internet as an alternative to shopping in the store. Many retail stores implement the application of electronic commerce (e-Commerce) transactions to allow the sale of products or services to consumers via the Internet in a very straight-forward manner. Until recently, there are little research had been undertaken into the implementation process of e-Commerce implementation, especially to that of business-to-customer (B2C). Seeing the complexity of the process of B2C implementation, this research tries to explore all possible factors influencing e-Commerce implementation in the extant of B2C literature. Based on the content analysis approach, the factors that influence e-Commerce implementation process are (1) compatibility; (2) complexity; (3) vendor capability; (4) business process re-engineering; (5) top management support; (6) organizational structure; (7) system champion; (8) communication; (9) resistance to change and (10) customer requirements. The paper concludes with three crucial issues that need to be clarified before these factors can be used for further actions: (1) the practical definition of implementation process that is capable to encapsulate the technological and organizational factors in implementing B2C e-Commerce applications; (2) the relationships that combine together the technological and organizational factors in the process of B2C e-Commerce implementation; and (3) the appropriate research approach to investigate B2C e-Commerce implementation process.